In vivo Neurological, Analgesic and In vitro Antioxidant and Cytotoxic Activities of Ethanolic Extract of Leaf and Stem Bark of Wedelia chinensis (Bangladesh Pharmaceutical Journal, 2019)
Wedelia chinensis is a widely used anti-inflammatory and hepatoprotective medicinal plant in Bangladesh. In this study, analgesic, neurological, antioxidant and cytotoxic activities of the ethanolic extract of leaf and stem bark of W. chinensis were investigated. Oral administration of the ethanolic extract of W. chinensis (200- and 300-mg/kg body weight) was investigated on animal model for neurological activity using open field test and hole cross test. Acetic acid induced writhing method was used to assess the analgesic activity. DPPH (1,1-diphenyl, 2-picryl hydrazyl) radical scavenging assay was used for determining the antioxidant activity, while brine shrimp lethality bioassay was used for investigating cytotoxicity. The ethanol extract of the plant produced significant reduction (P